Adeno-associated virus-mediated gene transfer of a secreted decoy human macrophage scavenger receptor reduces atherosclerotic lesion formation in LDL receptor knockout mice. - Jalkanen, J; Leppänen, P; Pajusola, K; Närvänen, O; Mähönen, A; Vähäkangas, E; Greaves, D; Büeler, H; Ylä-Herttuala, S (2003)
Macrophage scavenger receptors (MSR) promote atherosclerotic lesion formation, and modulation of MSR activity has been shown to influence atherosclerosis. Soluble receptors are effective in inhibiting receptor-mediated functions in various diseases. We have generated a secreted macrophage scavenger receptor (sMSR) that consists of the bovine growth hormone signal sequence and the human MSR A I extracellular domains. sMSR reduces degradation of atherogenic modified low-density lipoproteins and monocyte/macrophage adhesion on endothelial cells in vitro. To test long-term effects of sMSR, atherosclerosis-susceptible LDLR knockout mice were transduced via the tail vein with an adeno-associated virus (AAV) expressing sMSR or control enhanced green fluorescent protein (EGFP), and a Western-type diet was started. Gene transfer caused a temporary elevation in alkaline phosphatase and aspartate amino transferase values without a change in C-reactive protein. sMSR protein was detected in the plasma of the transduced mice by a specific ELISA 6 months after the gene transfer. AAV-mediated sMSR gene transfer reduced atherosclerotic lesion area in the aorta by 21% (P < 0.05) compared to EGFP-transduced control mice. Even though eradication of established disease was not possible, atherosclerotic lesion formation could be modified using AAV-mediated gene transfer of the decoy sMSR.